A creative approach to engaging students as partners at faculty level of the institution. (2016) - Lees, Becky; Garner, Wendy; Flectcher, Matthew; Gradwell, Naomi; Harris, Megan; Heathcote, Mike; Lawrence, Kerry; Medlock, Bethan; Wright, Emily
No abstract available